Development and implementation of the MobILcaps application for the teaching and development of information literacy in Higher Education - Mariscal, David Caballero; Pinto, María; Segura, Alicia (Applied Engineering and Technology, 2023)
This paper aims at develop, implement and evaluate the effectiveness of the MobIlCaps mobile application. On the basis of cognitive, constructivist and connectivist theories, it has been developed on an instructional design model, based on the user experience. In the context of mobile teaching in higher education, an innovative application is proposed for the self-learning of information literacy by students of Social Sciences. With the collaboration of both teachers and students, the application was developed, following the ADDIE model, through the phases of analysis, design, development, implementation and evaluation. The last phase provided the improvement proposals for the optimization of the final version of the tool, a progressive open access website. The application is organized into six capsules that follow the framework of ACRL (2015): learn, search, evaluate, create, research and disseminate. It includes multimedia resources in the form of microcontents that highlight readability, organization and visualization as characteristics. The app focuses on the user and is a relevant instrument to facilitate teaching The different analyses, followed by proposals for improvement and revisions, led to the achievement of a very useful application for students, teachers and library